GAYA KEPEMIMPINAN KEPALA SEKOLAH DI SD NEGERI BARINGIN KABUPATEN TAPANULI SELATAN - Abdilah BM, Alan Sayid; Hidayati, Dian; Hanama, Akhmad (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This research aims to describe the leadership style of school principals and the factors that influence the leadership behavior of school principals at SD Negeri Baringin, South Tapanuli Regency. This research is a type of qualitative research with a descriptive analytical approach. The results of the research show that, First, the leadership style of the principal of Baringin State Elementary School, South Tapanuli Regency is democratic, this can be seen from the role of the principal as educator, manager, administrator, supervisor, leader, innovator and motivator. Second, school principals are quite successful in improving the performance of educators and educational management. This is proven by the good competence of educators. Improving education management standards is also progressing well, namely through the stages of program planning, implementation of work plans as well as monitoring and evaluation. Third, supporting and inhibiting factors for implementing the school principal's leadership style in improving the performance of educators and educational management.Â